Bangladesh's Climate Vulnerability and Overseas Migration: Navigating Challenges and Paving the Way Forward - Tushar, Aminul Hoque; Parvin, Rawnaq Ara (CV. Literasi Indonesia, 2024)
Bangladesh ranks seventh on the Global Climate Risk Index 2021, which identifies the nations most susceptible to natural catastrophes, demonstrating how sensitive the country is to both climate change and natural disasters. Millions of people are forced to migrate to neighboring cities and urban areas in search of work and a living each year as a result of climate change and natural disasters such as river bank erosion, salinity intrusion, floods, cyclones, and landslides in Bhola, Khulna, Bagerhat, Patuakhali, and Gaibandha. Urban life is strained by this influx, especially in terms of housing, water supply, and sanitation. Many of these individuals also seek overseas employment as a means of survival. While numerous organizations, including government institutions, are working to promote safe and regular international migration and overseas employment, a portion of these individuals fall prey to labor trafficking due to a lack of information, monitoring, and services from the administration. Additionally, communities in climate-risk areas are ultimately forced to choose between internal and international migration due to the sluggish adoption of climate-resilient agricultural methods and technologies, as well as the dearth of technical and vocational education options. For these regions of significant natural disasters and climate change, the government has to provide more secure migration policies and encourage productive remittance investment.